2020
DOI: 10.3389/fchem.2020.00264
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Diguanylate Cyclase (DGC) Inhibitors Mitigating Bacterial Biofilm Formation

Abstract: The majority of bacteria in the natural environment organize themselves into communal biofilms. Biofilm formation benefits bacteria conferring resistance to harmful molecules (e.g., antibiotics, disinfectants, and host immune factors) and coordinating their gene expression through quorum sensing (QS). A primary signaling molecule promoting bacterial biofilm formation is the universal second messenger cyclic di-GMP. This dinucleotide predominantly controls the gene expression of motility, adhesins, and capsule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…cholerae due to their impact on the c-di-GMP signaling. These molecules exert their function via binding to c-di-GMP directly, affecting the enzymatic activity of DGCs that synthesize c-di-GMP, or mimicking c-di-GMP as a competitor in bacteria [ 157 , 158 , 159 , 160 ]. However, similar studies have not been reported in plant pathogenic bacteria, and the idea of using small molecules that target c-di-GMP for the management of plant diseases needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…cholerae due to their impact on the c-di-GMP signaling. These molecules exert their function via binding to c-di-GMP directly, affecting the enzymatic activity of DGCs that synthesize c-di-GMP, or mimicking c-di-GMP as a competitor in bacteria [ 157 , 158 , 159 , 160 ]. However, similar studies have not been reported in plant pathogenic bacteria, and the idea of using small molecules that target c-di-GMP for the management of plant diseases needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, various classes of diguanylate cyclases inhibitors have been developed. These include GTP or c-di-GMP analogs, which inhibit diguanylate cyclases in the active site and an allosteric site, respectively (Cho et al, 2020). Small molecule inhibitors of diguanylate cyclases have also been discovered using high-throughput in vitro and in silico screening (Cho et al, 2020), although activities tend to be modest.…”
Section: C-di-gmp Signalingmentioning
confidence: 99%
“…These include GTP or c-di-GMP analogs, which inhibit diguanylate cyclases in the active site and an allosteric site, respectively (Cho et al, 2020). Small molecule inhibitors of diguanylate cyclases have also been discovered using high-throughput in vitro and in silico screening (Cho et al, 2020), although activities tend to be modest. Stimulating activity of phosphodiesterases has been accomplished using nitric oxide donors such as sodium nitroprusside, leading to dispersal of P. aeruginosa biofilms (Barraud et al, 2006).…”
Section: C-di-gmp Signalingmentioning
confidence: 99%
“…While the inhibitors discussed are not a comprehensive list, they represent a wide range of diverse biofilm inhibitors with differing methods of discovery and inhibitory targets. As there is a growing interest in biofilms as antimicrobial targets, additional biofilm inhibitors and their known action mechanisms have been discussed in recent reviews, including synthetic biofilm inhibitors such as the phenazine and amino-immidozole inhibitor classes [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%